1991
DOI: 10.1002/j.2161-0045.1991.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

The Opinions of Minorities About Preparing for Work: Report of the Second NCDA National Survey

Abstract: A report of the 1989 NCDA survey of the perceptions of American adults of their career planning, the nature of their workplaces, and the availability of and utility of occupational information is presented. The survey, which was administered by the Gallup Organization, included an oversampling of Hispanics, African Americans, and Asian‐Pacific Islanders. Although the results for all groups including Whites are presented, the emphasis is upon the perceptions of minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…These include less confidence in one's abilities (e.g., job seeking self-efficacy, career-related self-efficacy), less career exploration, more career indecision, self (normative) stereotypes about the types of jobs they are best suited for, communication barriers (e.g., mode of communication for the deaf, language barriers for members of minority groups), and external constraints on career options due to issues such as childcare and eldercare duties (Betz, 1993;Bowman, 1995;Brown et al, 1991;Eden & Aviram, 1993;Feldman et al, 1994;Hackett & Lonborg, 1993;Hall, 1986;Russell, 1994;Stone & Colella, 1996;Strohmer, Czerlinsky, Menz, & Engelkes, 1984). Interestingly, research suggests that many of these issues are similar for those with diverse work status and diverse surface characteristics.…”
Section: Career-related Issues Facing Diverse Employeesmentioning
confidence: 98%
See 2 more Smart Citations
“…These include less confidence in one's abilities (e.g., job seeking self-efficacy, career-related self-efficacy), less career exploration, more career indecision, self (normative) stereotypes about the types of jobs they are best suited for, communication barriers (e.g., mode of communication for the deaf, language barriers for members of minority groups), and external constraints on career options due to issues such as childcare and eldercare duties (Betz, 1993;Bowman, 1995;Brown et al, 1991;Eden & Aviram, 1993;Feldman et al, 1994;Hackett & Lonborg, 1993;Hall, 1986;Russell, 1994;Stone & Colella, 1996;Strohmer, Czerlinsky, Menz, & Engelkes, 1984). Interestingly, research suggests that many of these issues are similar for those with diverse work status and diverse surface characteristics.…”
Section: Career-related Issues Facing Diverse Employeesmentioning
confidence: 98%
“…Several methods have been used to assess the validity of this instrument, including factor analysis of the three subscales, content validity of the items based on Tiedeman and O'Hara's (1963) theory of career development and Dinklage's (1969) taxonomy of decision-making styles, and concurrent validity evidence. Many diverse groups experience difficulty in career decision making due to lack of exposure to different career options and less confidence in their career decision-making skills (Brown et al, 1991;Strohmer et al, 1984). Thus, the Choosing a Career and Choosing a Major scales may have the most utility for diverse individuals interested in exploring career options in the career entry or re-entry stages.…”
Section: Assessment Of Career Decision Makingmentioning
confidence: 98%
See 1 more Smart Citation
“…The need for career assistance, particularly career information (Brown, Minor, & Jepsen, 1991), may be heightened for African-American clients because of their relative inaccessibility to educational and occupational opportunities. Inferior educational opportunities and subsequent job opportunities, stereotypes about which occupations are appropriate, overt and covert discrimination, and limited availability of role models, all lead to the perception of a restricted opportunity structure.…”
Section: General Issues In Career Counseling Withmentioning
confidence: 98%
“…In the National Career Development Association's national survey, Brown, Minor, and Jepsen (1991) reported that of the four racial and ethnic groups investigated, African American respondents indicated a greater need for career planning and information. The survey revealed that African Americans &dquo;more frequently reported needing assistance with making career decisions in the year prior to the survey, taking the only job available, needing assistance in getting occupational information, wanting to see occupational information improved, perceiving discrimination on the job, expecting to leave their current career, and recommending greater focus on career development activities in the schools&dquo; (p. 16).…”
mentioning
confidence: 97%